Fish aggregating devices drift like oceanographic drifters in the near-surface currents of the Atlantic and Indian Oceans. (February 2019) - Imzilen, T.; Chassot, E.; Barde, J.; Demarcq, H.; Maufroy, A.; Roa-Pascuali, L.; Ternon, J-F.; Lett, C.
Highlights: We use drifting Fish Aggregating Devices (FADs) to derive near-surface ocean currents. FADs and oceanographic drifters have similar velocities in the Indian Ocean (IO). FADs have lower velocities than oceanographic drifters in the Atlantic Ocean (AO). We hypothesize that longer FAD tails in the AO than in the IO slow them down. Fisher-collected data can become a major contributor of oceanographic information. Abstract: Knowledge of ocean surface dynamics is crucial for oceanographic and climate research. The satellite-tracked movements of hundreds of drifters deployed by research and voluntary observing vessels provide high-frequency and high-resolution information on near-surface currents around the globe. Consequently, they constitute a major component of the Global Ocean Observing System (GOOS). However, maintaining this array is costly and in some oceanic regions such as the tropics, spatio-temporal coverage is limited. Here, we demonstrate that the GPS-buoy equipped fish aggregating devices (FADs) used in tropical tuna fisheries to increase fishing success are also capable of providing comparable near-surface current information. We analyzed millions of position data collected between 2008 and 2014 from more than 15, 000 FADs and 2, 000 drifters, and combined this information with remotely-sensed near-surface current data to demonstrate that the surface velocity components of FADs and drifters are highly correlated in the Atlantic and Indian Oceans. While it was noted that the subsurface structures of FADs did slow them down relative to the drifters, particularly in the Atlantic Ocean, this bias was measurable and could be accounted for in future studies. Our findings show that the physical meteorological and oceanographic data collected by fishermen could provide an invaluable source of information to the GOOS. Furthermore, by forging closer collaborations with the fishing industry and ensuring their contributions to global ocean databases are properly acknowledged, there is significant scope to capture this data more effectively.